THE FORM OF GOVERNMENT OF A DEMOCRATIC STATE ON THE BACKGROUND OF CRISIS POLITICAL AND INSTITUTIONAL DESIGN - ALEKSEENKO, Artem (Fìlosofìâ ta polìtologìâ v kontekstì sučasnoï kulʹturi, 2024)
The article is devoted to the study of the peculiarities of the form of government as a structural basis for the exercise of power, formed within the framework of constitutional law, under the condition of representation of the main socio-economic groups of society. The purpose of the study is to establish the peculiarities of the form of state government as a factor in the formation of democratic institutional design. Features of the form of government as a factor of institutionalization of relations between authorized centers of power are characterized. It was emphasized that the modernization of the form of government in the political agenda may indicate a lack of deep consensus regarding the development of the political system. The significance of changes for institutional design within the evolution of the form of state government, which depends on the level of satisfaction of the requirements and needs of key political players, is analyzed. The significance of the political experience of Ukraine, which during the last decades has shown that political expediency is a more significant principle than considerations of preserving constitutional stability, is revealed. It was found that the existence of the current form of government in Ukraine is the result of the evolution of certain institutions, first of all, the institution of the presidency. In the context of the experience of the countries of Central and Eastern Europe, the assessment of the crisis phenomena of 2008 and 2010 becomes important, in particular the pressure of the demands of socio-economic balancing, which caused the “internal national reading” of the functioning of the form of government. It is revealed that the use of the existing potential of the form of government to ensure advantages in political competition led to the authoritarianization of the institution of the prime minister in modern Hungary. It has been proven that the international community’s fixation on the deterioration of the state of human rights protection has become a clear evidence of the influence of the form of government on inter-institutional interactions, in particular, in increasing the pressure of public authorities on civil society. It was established that the contradictions between high standards and the demands of the consumer society caused the support of right-wing conservative populist political forces. It was found that the situation in modern Slovakia shows that the parliamentary republic as a form of government also ensured the transition to democracy and the observance of democratic procedures. It was established that the trends of “non-normative” use of the power potential of the form of state government may indicate the search for a national model of balance between branches of government and key officials. It was concluded that a high level of self-regulation in the political system corresponds to a high level of civil political activity, responsibility and consensus of political elites, professionalism of the political class as a whole.